Effect of one-week supplementation of Citrulline-malate, L-arginine and their combination on CK, LDH and CRP levels in male wrestlers following simulated wrestling test - Shakib, Amir; Amir sasan, Ramin; Vakili, Javad (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2021)
Background: The aim of this research was to evaluate the effect of one-week supplementation of citrulline-malate, L-arginine and their combination on aerobic and anaerobic powers, CK, LDH and CRP levels in male wrestlers. Methods: In this experimental study, 40 male wrestlers (aged 19-25 years; weight 60-90 kg; body fat percent 12-20%) in a randomized and double-blind design were divided in four equal citrulline-malate (Cit; 4g/days), L-arginine (Arg; 4g/days), their combination (2g/days Arg + 2g/days Cit) and placebo (dextrose; P) group. Before and after supplementation one week period, all subjects were participated in a competition like wrestling. Each test consisted of two 3 min periods of arm-cranking at maximal executable cadence against resistance of 0.1 kg ∙ kg−1 body mass interspersed with 30-s recovery periods between consecutive tests. Blood samples were obtained in the 4 phases: one hour before and 5 min after two competitions like wrestling protocols. Creatine kinase (CK), C-reactive protein (CRP) and lactate dehydrogenase (LDH) were analyzed. Change any of the parameters (mean and standard deviation) of four stages repeated ANOVA and post hoc tests. The significance level was set at p<0.05. Results: Based on the present results, the Cit and Arg + Cit supplementation attenuated the exercise-induced increase in response of CK (p<0.05). However, the Arg supplementation had not any significant effect on the exercise-induced increase response of serum CK. Also, the Arg, Cit and Arg + Cit supplementation had not any significant effect on the exercise-induced increase response of total serum LDH and CRP. Conclusion: Based on the present results, it can be concluded that the one week citrulline-malate with L-arginine supplementation is more effective than the citrulline-malate or L-arginine supplementation to overcome the exercise-induced adverse responses in some muscle injury parameters. Therefore, combination of citrulline-malate and L-arginine supplementation is recommended to reduce exercise-induced adverse consequences.